Analisis Proses Pembelajaran Daring Masa Pandemi COVID-19 Pada Guru Kelas 1 MI Bustanul Ulum Karangsuko - Rofiqoh Firdausi (Fakultas Tarbiyah, IAIN Fattahul Muluk Papua, 2020)
This study aims to analyze the online learning process, supporting factors as well as inhibiting factors for teachers in implementing online learning during the COVID-19 pandemic. This research was conducted at MI Bustanul Ulum Karangsuko Pagelaran Malang starting from early July to mid-July. This research uses descriptive qualitative method. The subjects used in this study were Madrasah Ibtidaiyah teachers at MI Bustanul Ulum Karangsuko. The data collection techniques used in this study were open questionnaires, semi-structured interviews, documentation and field notes. The result of this research is that the COVID-19 pandemic has a huge impact on the learning process, learning that is usually carried out directly is now being converted into online learning. Students feel bored and bored while carrying out learning. Online learning conducted for elementary school age children is deemed ineffective. There are several supporting factors for teachers in the online learning process, namely the availability of mobile phones, quotas and a stable internet network. In addition to supporting factors in online learning, there are also several factors hindering teachers in online learning. The inhibiting factors include not all students have cellphones and many parents are still busy working.